Safety of antenatal breastmilk expression from week 34 of pregnancy: a randomized controlled pilot study (The Express-MOM study) - Marie Bendix Simonsen; Sarah Bjerrum Bentzen; Sören Möller; Kristina Garne Holm; Christina Anne Vinter; Gitte Zachariassen (Maternal Health, Neonatology and Perinatology)
Abstract Background Mother’s own milk (MOM) is important as the first nutrition for preterm infants, but mothers often struggle to initiate milk production right after preterm birth. If antenatal breastmilk expression (aBME) does not induce preterm labor when performed before term age, it could promote nutrition with MOM right after preterm birth. In this pilot study, we aimed to investigate whether aBME induces preterm labor among healthy nulliparous women from week 34 of pregnancy, to examine if aBME promotes the availability of MOM right after birth and affects breastfeeding outcomes. Methods Women were randomized to aBME (10 min 2 × daily) from week 34 of pregnancy until birth or to the control group. Both groups had a breastfeeding consultation between week 33 and 34 of pregnancy and were followed until eight weeks after birth. The primary outcome was gestational age (GA) at birth. Secondary outcomes were the availability of MOM and exclusive breastfeeding rates from 24 h to eight weeks after birth. Ranksum test and a posterior plot for the probability of non-inferiority were applied to the primary outcome. The availability of MOM is reported as medians and IQR. Breastfeeding outcomes were analyzed with mixed effects logistic regression. Results One hundred forty-four pregnant women were eligible for participation, 51 were excluded, and 33 declined participation/did not answer inclusion phone calls. 60 women were included and randomized. Primary outcome data were available in 55 women (28 in intervention, 27 in control). We found no difference in GA at birth between the two groups: median (IQR), 40 + 1(39 + 5:41 + 2) in intervention vs. 40 + 2 (39 + 4:41 + 1) in control, p = 0.98. Antenatal expressed MOM was available at birth in most women in the intervention group (23/28, 82%), with a median of 52 mL during pregnancy. There was no statistically significant difference in breastfeeding outcomes. No adverse events were reported. Conclusions aBME performed by healthy nulliparous women from gestational week 34 did not induce preterm labor. In most women in the intervention group, MOM was available right after birth. The study results provide the basis for a trial among women at high risk for preterm birth. Trial Registration. clinicaltrials.gov (NCT05516199). Graphical Abstract